2011
DOI: 10.1016/j.pnpbp.2011.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Myricitrin, a nitric oxide and protein kinase C inhibitor, exerts antipsychotic-like effects in animal models

Abstract: Myricitrin is a nitric oxide (NO) and protein kinase C (PKC) inhibitor that has central nervous system activity, including anxiolytic-like action. Nitric oxide inhibitors blocked the behavioral effects of apomorphine, suggesting an antipsychotic-like effect. Furthermore, PKC inhibition reduced psychotic symptoms in acute mania patients and blocked amphetamine-induced hyperlocomotion, suggesting a potential antipsychotic-like effect. The present study evaluated the effects of myricitrin in animal models that as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 57 publications
1
26
0
Order By: Relevance
“…These data demonstrated that myricitrin effectively inhibits H/R-induced apoptosis and provides further evidence supporting its anti-apoptotic role (Qin et al, 2015;Zhang et al, 2016). Myricitrin interacts with proteins, such as PI-3 kinase, nitric oxide synthase (NOS), PKCα, and PKCε (Pereira et al, 2011;Schwanke et al, 2013;Qin et al, 2015). In addition, previous studies have demonstrated that myricitrin potently inhibits calcium transport, likely through the interaction of the phenolic groups of this flavonoid with the Ca 2+ transporting protein (Thiyagarajah et al, 1991;Meotti et al, 2007).…”
Section: Discussionsupporting
confidence: 55%
“…These data demonstrated that myricitrin effectively inhibits H/R-induced apoptosis and provides further evidence supporting its anti-apoptotic role (Qin et al, 2015;Zhang et al, 2016). Myricitrin interacts with proteins, such as PI-3 kinase, nitric oxide synthase (NOS), PKCα, and PKCε (Pereira et al, 2011;Schwanke et al, 2013;Qin et al, 2015). In addition, previous studies have demonstrated that myricitrin potently inhibits calcium transport, likely through the interaction of the phenolic groups of this flavonoid with the Ca 2+ transporting protein (Thiyagarajah et al, 1991;Meotti et al, 2007).…”
Section: Discussionsupporting
confidence: 55%
“…Consistent with previous reports [16], our results showed that myricitrin increased HO-1 and NQO-1 expression, activated Akt phosphorylation and promoted Nrf2 signaling. Recent researches have reported that myricitrin can effectively inhibit protein kinase C pathways, which are mostly focus on antipsychotic effects of the agent [37,38]. It is highly limited to search for the related literature on myricitrin, as a PKC inhibitor to fight against apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, our observations on the protective role of myricitrin and HAE on DNA could be attributed to their potential effect on gene expression and/or its antioxidant activity. Moreover, Pereira et al (2011) reported that myricitrin is a nitric oxide and protein kinase C inhibitor that exerts anti-psychotic and anti-anxiolytic-like effects. Thus, further deep research needs to be conducted to introduce the bioactive myricitrin and A. amara leaves to the market as non-convential source of fertility regulating herbal drug with less deleterious side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Active constituent and plant material administration Myricitrin (major compound) was administrated orally at a dose of 30 mg/kg bw/d (1/10 of LD 50 300 mg) (Pereira et al 2011). Its chemical purity was > 95%, determined by HPLC.…”
Section: Biological Investigationmentioning
confidence: 99%